Genetic basis of rhizoid development in the liverwort Marchantia polymorpha - Honkanen, S (2015)
The evolution of specialised rooting structures was one of the key morphological innovations that allowed the first multicellular plants to colonise land more than 470 million years ago. The first land plants likely resembled modern bryophytes with a rooting structure that consists of filamentous rooting cells called rhizoids, which are morphologically similar to the root hairs of vascular plants. This thesis describes identification of genes required for rhizoid development in a model bryophyte, the liverwort Marchantia polymorpha. The aim was to identify the conserved and novel aspects of the gene regulatory networks for filamentous rooting cell development in land plants. Agrobacterium-mediated T-DNA transformation of haploid M. polymorpha spores was used to generate 150,000 M. polymorpha T-DNA insertion lines, which were screened for defects in rhizoid development. 204 rhizoid defective mutants were isolated which allowed identification of 25 genes required for M. polymorpha rhizoid development. The role of the class I RSL (ROOT HAIR DEFECTIVE SIX-LIKE) genes as positive regulators of root hair and rhizoid differentiation was found to be conserved between liverworts and vascular plants. This suggests that the class I RSL gene mechanism is ancient and originated before the two lineages diverged more than 440 million years ago. Furthermore, the M. polymorpha class I RSL gene MpRSL1 is required for development of gemmae and mucilage papillae, which similarly to rhizoids form from single epidermal cells that elongate to form an outgrowth. Moreover, MpRSL1 is under negative feedback regulation of the FEW RHIZOIDS1 (FRH1) microRNA. Many genes required for rhizoid elongation were similar with those required for root hair elongation, suggesting that these genes are likely to have been part of the genetic network downstream of class I RSL genes in the common ancestor of liverworts and vascular plants.